2022
DOI: 10.1039/d2cc01792j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic and genetic targeting of a red-emitting molecular calcium indicator

Abstract: We introduce a strategy for the fluorogenic and genetic targeting of a calcium indicator by combining a protein fluorogen with the BAPTA sensing group. The resulting dual-input probe acts like...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We have previously shown that small viscosity-sensitive molecular rotors could be used as fluorogenic HaloTag probes and used as a plaftform to build a dual-input calcium sensor. [25][26][27][28] We have adapted this approach to design a dual-input pH probe by exploring GFP-based chromophore structures that already possess pH-sensitive properties due to their phenol group and are based on a flexible molecular rotor structure that should also be activated by reaction with HaloTag. However, the pKa of the isolated GFP chromophore is too high for the biological pH range of exocytosis events.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that small viscosity-sensitive molecular rotors could be used as fluorogenic HaloTag probes and used as a plaftform to build a dual-input calcium sensor. [25][26][27][28] We have adapted this approach to design a dual-input pH probe by exploring GFP-based chromophore structures that already possess pH-sensitive properties due to their phenol group and are based on a flexible molecular rotor structure that should also be activated by reaction with HaloTag. However, the pKa of the isolated GFP chromophore is too high for the biological pH range of exocytosis events.…”
Section: Resultsmentioning
confidence: 99%
“…reported the sensor Ca‐DIP, based on a BAPTA‐functionalized fluorogenic molecular rotor, which also exploits fluorogenicity to gate sensor function (Figure 6d). [74] While the calcium sensitivity of this dye is similar to that of the JF and MaP‐based sensors, the brightness is lower, primarily due to the fluorophore scaffold.…”
Section: Functional Fluorophore Ligandsmentioning
confidence: 90%
“…Because of these advantages, fluorogenic reactions are ideal reactions for chemical biology applications. Additionally, after the fluorogenic reaction, a very strong fluorescence signal can be obtained; the starting materials do not need to be fluorescent or weakly fluorescent, which is of particular interest for in vivo labeling in bioconjugation, such as labeling and sequencing of nuclear acids and labeling of proteins, lipids, glycans, and others . In addition, enzyme-triggered bioorthogonal cleavage fluorogenic reactions have attracted wide attention because of their high biocompatibility, fast reaction rate, and robustness. These fluorogenic reactions can also be applied in detecting and acting as no-washing probes for fluorescent imaging. , …”
Section: Applications Of Fluorogenic Reactions In Chemical Biologymentioning
confidence: 99%